Community Needs Assessment among Latino Families in an Urban Public Housing Development. Issue 3 (August 2019) - Escobedo, Patricia; Gonzalez, Karina Dominguez; Kuhlberg, Jill; Calanche, Maria 'Lou'; Baezconde-Garbanati, Lourdes; Contreras, Robert; Bluthenthal, Ricky
Studies examining the health of public housing residents are limited. In response, community-based participatory research principles were used to develop an intervention aimed at improving health outcomes related to multifactorial risk behaviors among Latino families living in a low-income neighborhood. A two-part needs assessment was completed to guide the intervention: interviews with parents ( n = 10) and a group model building (GMB) workshop with youth and parents ( n = 40) to explore the parent-youth dynamic. Interviews indicated that poverty, youth disobedience, and inadequate communication between parents and youth led to parental stress. During the workshop, balancing and reinforcing feedback loops involving Communication, Trust, and Respect between youth and parents were identified. Based on these findings and collaboration with a community advisory board, a bilingual, mindfulness-based meditation intervention was designed to address community needs: positive parent-child interaction emphasizing trust and communication, stress reduction, and family well-being.